Impact of nanoparticles on amyloid peptide and protein aggregation: a review with a focus on gold nanoparticles. Issue 45 (18th September 2018) - John, Torsten; Gladytz, Anika; Kubeil, Clemens; Martin, Lisandra L.; Risselada, Herre Jelger; Abel, Bernd
Abstract : The accelerating and inhibiting effects of nanoparticles on amyloid peptide aggregation are discussed for varying nanoparticle and peptide properties in the context of recent studies. Abstract : Society is increasingly exposed to nanoparticles as they are ubiquitous in nature and introduced as man-made air pollutants and as functional ingredients in cosmetic products as well as in nanomedicine. Nanoparticles differ in size, shape and material properties. In addition to their intended function, the side effects on biochemical processes in organisms remain unclear. Nanoparticles can significantly influence the nucleation and aggregation process of peptides. The development of several neurodegenerative diseases, such as Alzheimer's disease, is related to the aggregation of peptides into amyloid fibrils. However, there is no comprehensive or universal mechanism to predict or explain apparent acceleration or inhibition of these aggregation processes. In this work, selected studies and possible mechanisms for amyloid peptide nucleation and aggregation, in the presence of nanoparticles, are highlighted. These studies are discussed in the context of recent data from our group on the role of gold nanoparticles in amyloid peptide aggregation using experimental methods and large-scale molecular dynamics simulations. A complex interplay of the surface properties of the nanoparticles, the properties of the peptides, as well as the resulting forces between both the nanoparticles and the peptides, appear to determine whether amyloid peptide aggregation is influenced, catalysed or inhibited by the presence of nanoparticles.